You are your own fairy tale - Lovelace, Amanda; Medeiros, Janaina (Freelance illustrator) (2022)
"Goodreads Choice Award-winning poet and bestselling author amanda lovelace presents the you are your own fairy tale series bound collection-- a beautiful and empowering trilogy that proves the only thing needed for a happily ever after is yourself. this elegantly bound edition of amanda lovelace's you are your own fairy tale trilogy includes all of the poems from break your glass slippers, shine your icy crown, & unlock your storybook heart that you fell in love with, as well as a new & never-before-seen introduction written by the author."--
Break your glass slippers -- Shine your ice crown -- Unlock your storybook heart.
Keywords: Lovelace, Amanda -- Poetry; Cinderella -- (Legendary character) -- Poetry; Cinderella -- (Legendary character); Lovelace, Amanda; Fairy godmothers -- Poetry; Fairy tales -- Poetry; Self-actualization (Psychology) in women -- Poetry; Fairy godmothers; Fairy tales; Self-actualization (Psychology) in women; Confessional poetry; Poetry; Confessional poetry; Poetry